A DEFENSE OF MILL'S ARGUMENT FOR THE "PRACTICAL INSEPARABILITY" OF THE LIBERTIES OF CONSCIENCE (AND THE ABSOLUTISM IT ENTAILS). Issue 2 (2020) - Jacobson, Daniel
Abstract: Mill advocated an unqualified defense of the liberty of conscience in the most comprehensive sense, which he understood to include not just the freedom to hold but also to express any opinion or sentiment. Yet considerable dispute persists about the nature of Mill's argument for freedom of expression and whether his premises can support so strong a conclusion. Two prominent interpretations of Mill that threaten to undermine his uncompromising defense of free speech are considered and refuted. A better interpretation can be founded on Mill's claim that the liberties of conscience are inseparable in practice. This claim can be defended with modern psychological insight about the nature of cognitive bias, and epistemological insight about why justification of creedal beliefs requires the universal toleration of opinion, insights which are largely anticipated by Mill. This argument is especially vital because it highlights the divide between classical liberalism and progressivism that has become a flashpoint in the current political debate over free speech.